Optical RIS Empowered Hybrid RF-VLC V2X Communication Systems: A Promising New Frontier for Smart Transportation Applications - Singh, Gurinder; Pal, Tathagat; Bohara, Vivek Ashok; Srivastava, Anand (International Symposium on Advanced Networks and Telecommunication Systems, 2023)
In this paper, we highlight the potential benefit of employing optical-RIS (O-RIS) for hybrid RF-VLC V2X communication networks for enhanced road safety applications, particularly at road intersections. We utilize various analytical tools of stochastic geometry to characterize the performance of the proposed framework subject to interference originating from neighbouring vehicles in terms of performance metrics such as outage probability, system goodput, and delay outage rate (DOR). All the derived analytical expressions have been corroborated through Monte Carlo simulations. Numerical results indicate that unlike existing classical RF with relaying solution, the proposed system setup shows a remarkable improvement in outage performance, throughput, and reduced latency. The proposed framework shall be beneficial in smart transportation applications in an urban environment or high-rise buildings, while meeting stringent ultra-high reliability and low latency requirements of 6G-V2X.